Survey research methods - Fowler, Floyd J. (Applied social research methods series, 2014)
Author Floyd Fowler provides students and researchers who want to collect, analyze, or read about survey data with a sound basis for evaluating how each aspect of a survey can affect its precision, accuracy, and credibility